GREENING THE TOURISTS: ANALYZING THE DRIVERS OF ENVIRONMENTALLY RESPONSIBLE TOURISM BEHAVIOR - Hadi, Prasetyo; Johan, Ahmad (Universitas Brawijaya, Indonesia, 2023)
The concept of green tourism has started to gain attention since it is seen as a practice that can reduce carbon emissions, environmental degradation, and detrimental impacts on the environment and tourists' activities. As the main actors within the tourism industry, tourists are also encouraged to start to have concerns for the environment when they visit a destination. This study attempts to identify the driving factors of tourists' environmentally responsible behavior by examining how green mindfulness, green knowledge, and individual green value of tourists influence attitudes towards green tourism, which then affect their intention and conduct to participate in green tourism. Through the quantitative method, this study employs a survey administered to 330 respondents who visited tourist destinations in West Java Province, Indonesia. The data obtained is analyzed using Structural Equation Modeling with Partial Least Square (SEM-PLS). Green mindfulness, knowledge, and individual values positively influence tourists' attitudes toward green tourism. Furthermore, attitude toward green tourism leads to the intention to participate in green tourism and eventually to environmentally responsible tourism behavior. This study forms a framework that explains the formation of pro-environmental behavior from visitors who have positive views, perceptions, and values toward the environment. Managers of tourist attractions can look for ways or alternatives to increase green mindfulness, knowledge, and value from tourists. Even though the visitors themselves can own this, the manager can grow it by providing information about green tourism on their website, social media, brochures, or information channels. This study offers new insight into how to boost the environmentally responsible behavior of tourists while visiting tourism destinations by utilizing the extended theory of planned behavior. It sheds light on green tourism from the side of the tourists by establishing the model of green tourists' behavior.